2010
DOI: 10.1007/s11604-009-0373-9
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic signal intensity changes on postmortem magnetic resonance imaging of the brain

Abstract: Postmortem MRI of the brain in all cases showed characteristic common SI changes. Global cerebral ischemia without following reperfusion and low body temperature explain these changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 31 publications
3
32
0
Order By: Relevance
“…[25][26][27][28] However, when postmortem examination employs the TI routinely used for living bodies, lesion detection by FLAIR imaging is diminished by unclear image contrast 18,19 caused by insufficient signal suppression of the CSF. Thus, parameters for FLAIR of PMMR imaging should be optimized for deceased subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[25][26][27][28] However, when postmortem examination employs the TI routinely used for living bodies, lesion detection by FLAIR imaging is diminished by unclear image contrast 18,19 caused by insufficient signal suppression of the CSF. Thus, parameters for FLAIR of PMMR imaging should be optimized for deceased subjects.…”
Section: Discussionmentioning
confidence: 99%
“…However, consensus regarding what constitutes a normal appearance on PMMR images is difficult because T 1 and T 2 values change according to body temperature. 12,[18][19][20] Therefore, acquisition of appropriate image contrast for deceased bodies at low temperatures re-*Corresponding author, Phone: +81-92-554-1255, Fax: +81-92-552-2707, E-mail: abe.k@junshin-u.ac.jp quires optimization of the parameters for PMMR imaging. Short-tau inversion recovery (STIR) and fluidattenuated inversion recovery (FLAIR) are typical sequences employed to suppress tissue signal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, PMMR imaging shows changes in SI in response to lowering body temperature after death. [12][13][14] It is difficult to achieve a consensus on the normal appearance of PMMR because these changes depend on temperature. Therefore, PMMR parameter optimization is needed to obtain appropriate image contrast for bodies at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…15 However, routine parameters for MR imaging of the living body do not suppress the SI of cerebrospinal fluid (CSF) of cadavers. 12,13,16 Tofts and associates reported that T 1 values of the CSF can be derived by measuring the diffusion coefficient of the CSF at low temperatures. CSF signals of the cadaveric brain can then be suppressed effectively by using an optimized inversion time (TI).…”
Section: Introductionmentioning
confidence: 99%